CONFLICT COMPETENCE DEVELOPMENT OF FUTURE PROFESSIONALS IN STAFF MANAGEMENT - Solovova, Natalya; Kalmykova, Olga; Sukhankina, Natallia (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
A high level of conflict competence is a crucial managerial proficiency characteristic in the staff management sphere, as constructive conflict and stress management positively contributes to the output of an organization. Research Objective: the rationale and development of methodological guidelines to improve conflict competence of master-students majoring in “HR management“, employees and executives; the creation of conflict counseling system. Research methods: surveys have been conducted to assess the relevance of conflict competence for the professional activities of HR managers. The paper contains the author’s concept of scientific methodological and educational support for the course “Conflict and Stress Management in an Organization”. The main problems of conflict competence development in the sphere of staff management are identified. Special attention is paid to the introduction of innovative active and interactive teaching methods that require motivational, methodological, technological, methodical and expertise willingness of the university lecturer. In this research study, the interrelation between the structural components of the lecturer’s methodical competence and the quality characteristics of master’s training programmes on staff management is revealed to prove their determinism. The paper provides the examples of various training assignments as well as the conflict competence development course description.